Agent-Driven Wireless Sensors Cooperation for Limited Resources Allocation - Abdel-Naby, Sameh; Muldoon, Conor; Zlydareva, Olga; O’Hare, Gregory (Intelligent Sensor Networks, 2013)
This chapter discusses the agents that announce the preferences of the assigned goal. It also discusses the supplier agents that take into consideration the preferences and the context provided to compete for service provision. The chapter provides an negotiation agents that maintain all of the allowed negotiation strategies and mediate between the earlier types of agents. An agreement is reached when the user agent succeeds to make a contract with one of the ISP agents and retrieves a configuration file that, eventually, the end user installs on its pocket device to get an Internet access through the best available ISP. The subject of this example deals directly with the concept of achieving seamless communications of biologically driven ambient assisted living with emphasis on health care. The chapter describes a health care–oriented example that is potentially a suitable testbed for future examination to our idea of integrating agent-based negotiation protocols with wireless sensor networks.